Lung cancer and occupational exposure: hospital-based case-control study - Christiane Brey; Dario Consonni; Leila Maria Mansano Sarquis; Fernanda Moura D'Almeida Miranda (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To analyze the relationship between occupation and lung cancer in patients at a national referral hospital for cancer care in southern Brazil. Method Hospital-based case-control study conducted between February and October 2019. Occupational histories were coded according to international classifications and translated into occupations associated with lung cancer (List A and B). The odds ratios were adjusted for smoking, with a 95% confidence interval, calculated by conditional logistic regression. Results 99 cases and 227 controls were included. Among men, the occupation of painters (list A) was associated with lung cancer (OR = 14.3; 95% CI: 1.8-116.5), there were no occupations in list B associated with lung cancer. In women, no increased risks were found. Conclusions It has been shown that exposure to occupational carcinogens among repair and construction painters increases the risk of lung cancer.